Evaluation and the appropriate policy level under the demands of sustainability - Thiemo W. Eser (European Regional Science Association (ERSA), 2002)
The federal states' (and partly also unitary states' with decentralised administrations) advantages such as additional division of power and the better consideration of regional preferences and fallacies such as the trap of too strong entanglements of all levels of government are well discussed in comparison to unitary states. Since the Brundtland Report sustainable development is strongly advocated as a guiding principle for policy making. The capability of states to deal with this sustainability much depends on whether the appropriate level of state is commissioned to deal with the issues in question. Starting with discussion of the traditional arguments of the assignment of tasks to governmental levels in federal states the paper develops the new demands deriving from sustainability. The paper searches for useful and applicable criteria for the investigation of the appropriate governmental level taking into account the three thematic dimension of economy, ecology and social aspects - and the (fourth) dimension of monitoring and governance. Two dimensions need to be considered in order to identify the most appropriate level for political action: How are social, economic and environmental effects spatially spread? Which existing level and institutions of governance are available to deal with these issues and do these institutions cover the demands referring to the criteria developed in the first part of the paper? The criteria allow to distinguish better and worse distribution of competences but important are also the following conditions which need to be also evaluated: firstly, representatives of all governmental levels recognise the limits but also the potentials in dealing with specific tasks under the demands of sustainability, secondly, they are able to delegate if limitations are apparent, thirdly, they develop a cooperative attitude and appropriate institutional infrastructure to deal which tasks involving different governmental levels and fourthly, new policy models are taken into consideration which consult stakeholder without conflicting with democratic rules and foundations of states.
Keywords: 330